(Ph4P)2[Be3(μ-OH)3(H 2O)6]Cl5: Crystal structure and DFT calculations (Ph4P)2[Be3(μ-OH)3(H 2O)6]Cl5: Kristallstruktur und DFT-Rechnungen - Puchta, Ralph; Neumüller, Bernhard; Dehnicke, Kurt (Zeitschrift für Anorganische und Allgemeine Chemie, 2009)
Bis(tetraphenylphosphonium)-tris(u-hydroxo) hexaaquatriberylliumpentachloride, (Ph4P)2[Be 3(μ-OH)3(H2O)6]Cl5 (1), was surprisingly obtained by reaction of (Ph4P)N 3· n H2O with BeCl2 in dichloromethane suspension, and subsequent crystallization from acetonitrile to give single crystals of composition 1- 5.25CH3CN. According to the crystal structure determination space group P1̄, Z = 2, lattice dimensions at 100 K: a = 1354.8(2), b = 1708.7(2), c = 1753.2(2) pm, α = 114.28(1)°, ß = 94.80(1,)°, γ = 104.51(1,)°, R1 = 0.0586] the [Be 3(μ-OH)3(H2O)6]3- cations form six-membered Be3O3 rings with boat conformation and distorted tetrahedrally coordinated beryllium atoms with the terminally coordinated H2O molecules. The structure ist characterized by a complicated three dimensional hydrogen-bridging network including O-H-O, O-H-Cl, and O-H-NCCH3 contacts. DFT calculations result in nearly planar [Be3(OH)3] six-membered ring conformations. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Beryllium; DFT calculations; Hydroxo complex